Pengaruh Kepemimpinan Transformasional Kepala Sekolah dan Aplikasi Ruang GTK Terhadap Kompetensi Pedagogik Guru SD Negeri se-Kecamatan Kunduran - Gilar Kholiq Permono; Soedjono Soedjono; Harto Nuroso (Cetta: Jurnal Ilmu Pendidikan, 2026)
Teacher pedagogical competence is a crucial factor in improving the quality of learning in primary schools, which is influenced by school leadership and the use of educational technology. This study aims to: (1) analyze the effect of principals’ transformational leadership on teachers’ pedagogical competence; (2) analyze the effect of the use of the Ruang GTK application on teachers’ pedagogical competence; and (3) analyze the simultaneous effect of both variables on teachers’ pedagogical competence. This study employed a quantitative approach with an ex post facto design. The population consisted of all public elementary school teachers in Kunduran District, Blora Regency, with a sample of 172 teachers determined using the Slovin formula and proportional random sampling technique. Data were collected using questionnaires, and the analysis included prerequisite tests (normality, linearity, homogeneity, multicollinearity, and heteroscedasticity) and hypothesis testing using simple and multiple regression analyses. The results show that: (1) principals’ transformational leadership has a significant effect on teachers’ pedagogical competence, contributing 41.8% with a correlation coefficient of 0.646; (2) the use of the Ruang GTK application has a significant effect, contributing 47.7% with a correlation coefficient of 0.691; and (3) simultaneously, transformational leadership and the use of the Ruang GTK application have a significant effect on teachers’ pedagogical competence, contributing 55.7% with a correlation coefficient of 0.750. In conclusion, improving teachers’ pedagogical competence can be achieved through strengthening principals’ transformational leadership and optimizing the use of the Ruang GTK application. Therefore, principals are encouraged to provide continuous guidance and support, while teachers should actively utilize digital platforms for ongoing professional development.